Business-community relationships for extractive industries: a case study in Peru - Ventura, Jose (2017)
Natural resource-based economies have long relied on foreign demand to fuel their growth. For instance, the extractive sectors in Peru have experienced a rapid expansion, driven by a rising demand for commodities. Alongside economic growth, extractive operations have triggered social and environmental concerns among the various stakeholders, thus resulting in either social conflict or a deterioration of the relationship between companies in the extractive industries and local communities. In this context, the purpose of this paper is to understand the relationships between companies in the extractive industries and rural families. This research uses the case-study method. The findings show that a trustful relationship is supported by a beneficiary-society approach that builds upon philanthropic and ethical types of relationships. Unlike the type of relationship based on economic or legal interests, a trust-based relationship offers avenues for managing social conflict that have yet to be explored.